METHOD OF DRYING TENGIRI CRACKERS USING INFRARED LIGHT EXPOSURE TO INCANDESCENT LAMPS AS AN ALTERNATIVE DRYED IN THE RAINY SEASON - Nurunnisak, Latifah; Latifah Kadarusman, Faza; Susilayati, Muslimah (Jurnal Saintifik (Multi Science Journal), 2025)
Conventional drying of fish crackers (kerupuk tengiri) relies heavily on sunlight, posing a significant challenge during the rainy season, hindering production and potentially leading to economic losses due to product quality degradation. This research aims to develop and test an alternative drying method using infrared light exposure from incandescent lamps for fish crackers, as an innovative solution for the rainy season. The research method involves designing a simple drying apparatus in the form of a can-oven, equipped with an incandescent lamp, electrical plug, and cables as heat conductors. Fish crackers, as the research object, are dried using this apparatus, and the results are compared with conventional drying. The research emphasizes the effectiveness of infrared radiation heat generated by the incandescent lamp in reducing the moisture content of the crackers. The results of this study are expected to demonstrate that infrared light exposure from incandescent lamps is effective as an alternative drying method, ensuring production continuity and improving the quality of fish crackers in Indonesia during the rainy season.